Efficient perovskite solar cells fabricated by manganese cations incorporated in hybrid perovskites. Issue 38 (18th September 2019) - Liu, Wei; Chu, Liang; Liu, Nanjing; Ma, Yuhui; Hu, Ruiyuan; Weng, Yakui; Li, Hui; Zhang, Jian; Li, Xing'ao; Huang, Wei
Abstract : Efficient perovskite solar cells fabricated by manganese cations incorporated in hybrid perovskites. Abstract : Halide perovskites have attracted much attention among the emerging photovoltaic materials due to their high efficiency, low cost and facile solution processing. However, the usual facile materials contain toxic Pb elements, which can pollute the environment and cause almost permanent damage to the earth and mankind. Therefore, the exploration of non/less-lead halide perovskites is urgent for the practical application of this photovoltaic technology. Here, perovskites with the formula MAPb1− x Mn x I3 (where x = 0, 5%, 12.5%, 25% and 50%) and 1% MnI2 excessive doped MAPbI3 were prepared. With 1% MnI2 excessive doping in MAPbI3, the perovskite film showed larger crystal sizes than that of a pristine MAPbI3 film. The optimization results from first-principles calculations revealed that Mn 2+ could be easily inserted into the interstices of octahedral [PbI6 ] 4− to restrain the generation of vacancy defects accompanying perovskite crystallization. These could improve the microcrystalline thin film quality during the annealing process and reduce carrier recombination. Eventually, the efficiency of the perovskite solar cells based on 1% MnI2 excessive doping was up to 19.09%, which was superior to 17.68% of the MAPbI3 -based devices. In addition, the MAPb1− x Mn x I3 (where x = 0, 5%, 12.5%, 25% and 50%) films possessed large grains and tunable bandgaps. Meanwhile, efficiency of 6.40% was still obtained when the substitution content was increased to 12.5%. Consequently, the perovskite solar cells based on Mn incorporation have enormous potentials for applications and provide a potential pathway for non/less-lead hybrid perovskite materials.